Quantum and Classical Phases in Optomechanics - Armata,F; Latmiral,L; Pikovski,I; Vanner,MR; Brukner,C; Kim,MS (Physical Review A, 2016)
The control of quantum systems requires the ability to change and read-outthe phase of a system. The non-commutativity of canonical conjugate operatorscan induce phases on quantum systems, which can be employed for implementingphase gates and for precision measurements. Here we study the phase acquired bya radiation field after its radiation pressure interaction with a mechanicaloscillator, and compare the classical and quantum contributions. The classicaldescription can reproduce the nonlinearity induced by the mechanical oscillatorand the loss of correlations between mechanics and optical field at certaininteraction times. Such features alone are therefore insufficient for probingthe quantum nature of the interaction. Our results thus isolate genuine quantumcontributions of the optomechanical interaction that could be probed in currentexperiments.